Defensive strategy and player sex impact heart-rate responses during games-based drills in professional basketball - Suárez-Iglesias, D.; Dehesa, R.; Scanlan, A. T.; Rodríguez-Marroyo, J. A.; Vaquera, A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Games-based drills (GBD) are the predominant form of training stimulus prescribed to male and female basketball players. Despite being readily manipulated during GBD, the impact of defensive strategy on the sex-specific demands of GBD remains unknown. Therefore, the aim of this study was to quantify and compare the heart-rate (HR) responses experienced during 5v5 GBD using different defensive strategies (man-to-man defense vs zone defense [ZD] formations) according to player sex. Method: HR was recorded in 11 professional male and 10 professional female basketball players while performing 5v5 GBD with different defensive strategies (man-to-man defense or ZD). HR-based training load was also calculated using the summated heart-rate zones model. Results: During man-to-man defense, mean HR (eta2p=.02), relative time (in percentage) spent working at 90% to 100% maximal HR (?2p=.03), and summated heart-rate zones (eta2p=.02) were greater (P < .05) in female players compared with males. During ZD, higher (P < .01) peak HR (eta2p=.07), mean HR (eta2p=.11), relative and absolute (in minutes) time spent working at 80% to 89% maximal HR (eta2p=.03 and .03, respectively) and 90% to 100% maximal HR ((eta2p=.12 and .09, respectively), and summated heart-rate zones (?2p=.19) were observed in female players compared with males. Conclusions: The defensive strategy employed during 5v5 full-court GBD influences HR responses and training load differently according to sex, where female players experience higher HR responses than males, especially when ZD are adopted. Basketball coaching staff can use these findings for the precise manipulation of team defenses during GBD to elicit desired cardiovascular stress on players.